Co-text and critical reading for international postgraduates in Australia. Issue 3 (3rd July 2022) - Zaini, Amin
Abstract: This research article reports on a study that investigated the associations between co-text and reading texts critically. Four international postgraduates at an Australian university, through purposive sampling, volunteered in a qualitative study (i.e. a collective case study). Data collection involved reading four texts, participating in individual interviews, and focus group discussions, while data analysis was executed through a thematic analysis which yielded co-text as a main theme. Co-text was subsequently studied through Foucault's theories of discourse, subjectivities, the power-knowledge complex and resistance. The findings propose that there are associations between co-text, meaning construction and critical reading. Participants' cognisance of co-text, owing to their academic and political identities, informed meaning construction and led them to resist text ideas for potential co-text manipulation and what was reported as deliberate inadequate information. Pedagogically, this study suggests that teachers explicitly instruct students on the workings of co-text when reading texts critically.